Generation of Quantum Beams in Large Clusters Irradiated by Super‐Intense, High – Contrast Femtosecond Laser Pulses. Issue 2 (31st January 2013) - Faenov, A. Ya.; Pikuz, T. A.; Fukuda, Y.; Skobelev, I. Yu.; Nakamura, T.; Bulanov, S. V.; Hayashi, Y.; Kotaki, H.; Pirozhkov, A. S.; Kawachi, T.; Chen, L. M.; Zhang, L.; et al.
Abstract A short review of our experimental studies on generation of photon and particle beams in submicron clusters irradiated by intense, high‐contrast (∼ 108–1010) femtosecond laser pulses is presented. It is shown that highlyefficient laser‐cluster interaction allows creating bright sources of X‐ray, high‐energy electron and ion beams. The examples of applications of femtosecond‐laser‐produced cluster plasmas (FLPCP) for X‐ray and ion beams radiography are presented. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)